2017
DOI: 10.1038/nature21406
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-kinase δ blockade increases genomic instability in B cells

Abstract: Activation-induced cytidine deaminase (AID) is a B-cell specific enzyme that targets immunoglobulin (Ig) genes to initiate class switch recombination (CSR) and somatic hypermutation (SHM)1. Through off-target activity, however, AID has a much broader impact on genomic instability by initiating oncogenic chromosomal translocations and mutations involved in lymphoma development and progression2. AID expression is tightly regulated in B cells and its overexpression leads to enhanced genomic instability and lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
91
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 44 publications
9
91
2
Order By: Relevance
“…Within the BCR signalosome, BTK and the PI3K p85α/p110δ dimer are required for maximal signaling output as measured by Ca 2+ flux, IκB degradation and Erk phosphorylation. Notably, BTK inhibition can reduce PI3K signaling output in B cells (Bojarczuk et al, 2016; Compagno et al, 2017; Saito et al, 2003), supporting the concept that PI3K and BTK cooperate in the signalosome rather than operating in a simple linear fashion. The functional link between BTK and p85α/p110δ is strongly supported by genetic evidence.…”
Section: Pi3k In Innate and Adaptive Immunitymentioning
confidence: 55%
“…Within the BCR signalosome, BTK and the PI3K p85α/p110δ dimer are required for maximal signaling output as measured by Ca 2+ flux, IκB degradation and Erk phosphorylation. Notably, BTK inhibition can reduce PI3K signaling output in B cells (Bojarczuk et al, 2016; Compagno et al, 2017; Saito et al, 2003), supporting the concept that PI3K and BTK cooperate in the signalosome rather than operating in a simple linear fashion. The functional link between BTK and p85α/p110δ is strongly supported by genetic evidence.…”
Section: Pi3k In Innate and Adaptive Immunitymentioning
confidence: 55%
“…107 However, the combination of ruxolitinib and the pan-PI3K inhibitor buparlisib was relatively disappointing. 108 More recent efforts in this area have focused on drugs that selectively target the d isoform of PI3K 109 ; however, the experience with idelalisib in B-cell malignancies tells a cautionary tale, with reports of induction of genomic instability in B cells 110 and of high rates of immune-mediated hepatotoxicity in previously untreated patients with chronic lymphocytic leukemia. 111 PRM-151 is recombinant human pentraxin-2, a naturally occurring plasma protein also known as serum amyloid P that inhibits fibrocyte differentiation.…”
Section: Jak2mentioning
confidence: 99%
“…The drugs idelalisib and ibrutinib target a B-cell-receptor signalling pathway and are used for cancer treatment; idelalisib and duvelisib (an investigational drug) both inhibit PI3Kδ, and ibrutinib inhibits BTK. Using mouse models and human cells, Compagno et al 2 observed that drug-mediated inhibition of the B-cell-receptor signalling pathway can increase the expression of AID, causing DNA mutations in non-immunoglobulin off-target genespotentially increasing the incidence of tumour-promoting mutations. Effects of drug use are shown in red.…”
Section: A Targeted Treatment With Off-target Risksmentioning
confidence: 99%
“…By contrast, targeted therapies are designed to block specific molecular pathways in cancer cells and induce tumour-cell death without causing DNA damage. On page 489, Compagno et al 2 report studies of mouse models and human cells showing that two targeted drugs that are commonly used instead of chemotherapy in the treatment of certain blood cancers unexpectedly increase DNA damage in both healthy cells and tumour cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation